KONSEP PENDIDIKAN PRANATAL, POSTNATAL, DAN PENDIDIKAN SEPANJANG HAYAT - Tri Andiyanto (Jurusan PGMI FTIK IAIN Metro Lampung, 2018)
Prenatal education is a conscious effort of parents to educate their children who are still in the womb of their wives. A conscious effort is specifically directed at both parents because the child in the womb is not yet possible to be educated, let alone taught, except by his own parents. Postnatal Education is human education in a family environment starting from human being born until the end of his life. All kinds of life sciences gained from the family are the result of the process of postnatal family education. From human being born, they have been taught how to face down, drink, eat, walk and even about religion. Lifelong learning provides learning opportunities fairly and broadly to everyone in accordance with the differences in interests, age, and learning needs of each. This opportunity is an opportunity that can be used for learning such as group learning activities, individual learning activities, and learning activities through social media. Learning activities can be carried out in various places, namely at work, worship houses; association buildings, schools, playgrounds, sports fields, youth arenas, study groups, hermitage, libraries, learning centers, institutions and so on.